A Facilitated Peer Mentoring Program With a Dedicated Curriculum to Foster Career Advancement of Academic Hospitalists - Doris Lin; R. Michelle Schmidt; Chirayu Shah; Andrew Caruso; Xiaofan Huang; Kristen A. Staggers; Joslyn Fisher (Association of American Medical Colleges, 2023)
Introduction In the field of hospital medicine, there is both a limited pool of senior faculty to mentor the rapidly growing number of junior faculty and a lack of career development curricula focused on scholarly activities specific to the needs of the hospitalist. These deficits have resulted in a disproportionately low number of academic hospitalists being promoted to associate and full professor. We implemented a facilitated peer mentoring program with a dedicated curriculum to foster career advancement of academic hospitalists. Methods We recruited 29 academic hospitalists and divided them into five small groups, each guided by one senior faculty. Peer members participated in a 9-month curriculum consisting of alternating large- and small-group sessions that reviewed topics important for academic advancement. Quantitative analysis assessed feasibility of the program, as measured by participation and knowledge improvement on curriculum topics, with pre- and postprogram surveys. Results Results demonstrated feasibility of the large-group sessions as measured through participation. Small-group participation was more variable. Pre- and postsurvey results showed significant knowledge improvement (p < .05) in nearly all of the curriculum topics. Discussion Currently, there is a gap in both mentorship and scholarly skills of academic hospitalists. Our facilitated peer mentoring program with a dedicated curriculum can be used as a framework for other hospitalist programs to support career development.